Nonlinear charge and energy dynamics of an adiabatically driven interacting quantum dot - Romero, Javier I.; Roura Bas, Pablo Gines; Aligia, Armando Ángel; Arrachea, Liliana del Carmen (American Physical Society, 2017)
Fil: Romero, Javier I.. Universidad Nacional de San Martín. Escuela de Ciencia y Tecnología; Argentina